Lupus Vasculitis: An Overview - Patrizia Leone (MDPI AG, 2021)
Lupus vasculitis (LV) is one of the secondary vasculitides occurring in the setting of systemic lupus erythematosus (SLE) in approximately 50% of patients. It is most commonly associated with small vessels, but medium-sized vessels can also be affected, whereas large vessel involvement is very rare. LV may involve different organ systems and present in a wide variety of clinical manifestations according to the size and site of the vessels involved. LV usually portends a poor prognosis, and a prompt diagnosis is fundamental for a good outcome. The spectrum of involvement ranges from a relatively mild disease affecting small vessels or a single organ to a multiorgan system disease with life-threatening manifestations, such as mesenteric vasculitis, pulmonary hemorrhage, or mononeuritis multiplex. Treatment depends upon the organs involved and the severity of the vasculitis process. In this review, we provide an overview of the different forms of LV, describing their clinical impact and focusing on the available treatment strategies.